“Las TIC en la enseñanza de lectoescritura en niños de primer año de básica de la escuela 3 de Diciembre del cantón Paltas, periodo 2024¨. - Diaz Carpio, Vanessa Dayana (2024)
The objective of this research is to analyze the relevance of ICT in the learning of reading and writing in first-year basic students of 3 de Diciembre school, period 2024. Currently, technology plays a really important role in education, offering a variety of resources that allow innovative activities to be carried out within the teaching and learning process. In the methodological design, a qualitative approach was assumed that will allow the results obtained during the implementation to be compared, in addition, the inductive-deductive, bibliographic and observational method was applied in each of the processes aimed at identifying ICT, which contribute to literacy teaching. The results were able to identify the effectiveness that the application of ICT in literacy could have, through the application of technological tools and resources. It is concluded that, by involving ICT in teaching activities, it makes easier for children to obtain and reinforce literacy in a positive, playful and innovative way. Keywords: Technology, comprehensive development, educational process, education, educational development